NCOG-13. TUMOR-RELATED MOLECULAR DETERMINANTS OF NEUROCOGNITIVE DEFICITS IN PATIENTS WITH DIFFUSE GLIOMA. (12th November 2021) - van Kessel, Emma; Berendsen, Sharon; Baumfalk, Anniek; Venugopal, Hema; Krijnen, Eva; Spliet, Wim; van Hecke, Wim; Giuliani, Fabrizio; Seute, Tatjana; van Zandvoort, Martine; Snijders, Tom; Robe, Pierre
Abstract: BACKGROUND: Cognitive impairment is a common and debilitating symptom in patients with diffuse glioma and is the result of multiple factors. We hypothesized that molecular tumor characteristics influence neurocognitive functioning (NCF), and we aimed to identify tumor-related markers of NCF in diffuse glioma patients. METHODS: We examined the relation between cognitive performance (executive function, memory and psychomotor speed) and intratumoral expression level of molecular markers, in treatment-naive patients with diffuse glioma. We performed a single-center study in a prospectively collected cohort, through a two-step design: (1) differential expression and gene set enrichment analysis (GSEA) to identify candidate oncogenetic markers for cognitive impairment in a hypothesis-free manner. Nineteen molecular markers of interest were derived from this set of genes as well as from prior knowledge; (2) correlation of cognitive performance (executive function, memory and psychomotor speed) to intratumoral expression level of these nineteen molecular markers, measured with immunohistochemistry. RESULTS: After correcting for tumor volume and location, we found significant associations, between expression level of CD3 and IDH on the one hand with psychomotor speed on the other; between IDH, ATRX, BDNF, CSNK2B, EAAT1, GAT-3, SRF and memory performance; and between IDH, P-STAT5b, CSNK2B and executive functioning. P-STAT5b, CD163, CD3 and SEMA3 were independently associated after further correction for histopathological grade. CONCLUSION: Several molecular characteristics of gliomas are independent determinants of patients' cognitive functioning. This suggests that besides tumor volume, location and histological grade, variations in glioma biology influence cognitive performance through mechanisms that include perturbation of neuronal communication. These results pave the way towards targeted cognition improving therapies in neuro-oncology.